Pregnancy in Charcot-Marie-Tooth disease: Data from the Italian CMT national registry. (15th December 2020) - Pisciotta, Chiara; Calabrese, Daniela; Santoro, Lucio; Tramacere, Irene; Manganelli, Fiore; Fabrizi, Gian Maria; Schenone, Angelo; Cavallaro, Tiziana; Grandis, Marina; Previtali, Stefano C.; Allegri, Isabella; Padua, Luca; et al.
Abstract : Objective: To collect information on frequency of pregnancy and delivery complications in Charcot-Marie-Tooth (CMT) disease and on CMT course during pregnancy. Methods: Through an ad hoc online questionnaire, we investigated pregnancy and neuropathy course in women with CMT adhering to the Italian CMT Registry. Data were compared to those of controls (recruited among friends and unaffected relatives) and the Italian (or other reference) population. Results: We collected data on 193 pregnancies from 86 women with CMT (age 20–73 years) with 157 deliveries (81.4%) after a mean of 38.6 gestational weeks. In women with CMT, there were no differences compared to controls (59 pregnancies and 46 deliveries from 24 controls) and the reference population for miscarriages (11.4%) and planned (21.0%) and emergency (14.0%) cesarean sections. We found a significantly higher frequency of placenta previa (1.6% vs 0.4%), abnormal fetal presentations (8.4% vs 4.5%), and preterm deliveries (20.3% vs 6.9%; most in week 34–36 of gestation) compared to reference populations. Excluding twins, newborn weight did not differ from the reference population. Postpartum bleeding rate in patients with CMT (2.1%) was similar to that of the general population (2.4%). CMT status worsened during 18 of 193 pregnancies (9.3%) with no recovery in 16 of them and with similar figures in the CMT1A and non-CMT1A subtypes. Conclusions: We observed higher rates of placenta previa, abnormal presentations, and preterm deliveries in CMT, but pregnancy outcome and newborn weight and health were similar to those of the reference populations. Worsening of CMT is not infrequent and occurs not only in CMT1A. Pregnant women with CMT should be monitored with particular care.